HUBUNGAN POLA TIDUR TERHADAP KONSENTRASI BELAJAR SISWA DI ELHAQQA QURANIC SCHOOL - Befri Yonandes; Munjiatun; Zariul Antosa (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The purpose of this research is to examine the relationship between sleep patterns and learning concentration of students at Elhaqqa Quranic School. This research employed a quantitative approach with a descriptive correlational method. The population and sample consisted of 20 fourth- and fifth-grade students selected using a saturated sampling technique. Data were collected through questionnaires on sleep patterns and learning concentration, and analyzed using normality tests, linearity tests, Pearson correlation, and simple linear regression with SPSS 23. The findings reveal that most students had moderate levels of both sleep patterns and learning concentration. Correlation analysis showed a very strong and significant relationship between sleep patterns and learning concentration, with correlation coefficients (r) ranging from 0.943 to 0.977 (p < 0.05). The coefficient of determination indicated that sleep patterns contributed between 89% and 95.4% to variations in students’ learning concentration.